DEVELOPMENT OF METACOGNITIVE ACTIVITIES TO INCREASE STUDENTS' INTEREST IN PHYSICS - Urinboev Mukhammadzokhir Iqboljon ugli (International Journal of Pedagogics, 2024)
This article is dedicated to exploring ways to increase students' interest in physics through the development of metacognitive activities. The article provides a detailed analysis of the essence of metacognitive approaches and their significance in physics education. It also demonstrates how metacognitive strategies can be applied to enhance students' interest in physics. The experimental and theoretical sections highlight methods for managing the learning process, applying theoretical knowledge in practice, and deepening the understanding of concepts. The article offers guidance for teachers and education specialists on how to implement metacognitive approaches in their physics lessons.